Growth and yield response of wheat (Triticum aestivum L.) to tillage and row spacing in maize-wheat cropping system in semi-arid region - Shafaqat Ali; Muhammad Shahid Ibin-i Zamir; Mujahid Farid; Muhammad Ahsan Farooq; Muhammad Rizwan; Rehan Ahmad; Fakhir Hannan (Eurasian Journal of Soil Science, 2016)
Tillage practices and row spacing can be manipulated to optimize spatial distribution and plant growth, therefore maximizing sunlight, soil water use efficiency, nutrients and grain yield on sustainable basis. A field study was conducted to determine the effect of tillage and row spacing on growth and yield of wheat (Triticum aestivum L.) at Agronomic Research Area, University of Agriculture, Faisalabad, Pakistan during wheat season. The treatments were comprised of two tillage practices viz. zero tillage and conventional tillage and four row spacing viz. 15 cm, 20 cm, 25 cm and 30 cm. The experimental results revealed that zero tillage significantly enhanced the plant height, tillers m-2, spike length, 1000 kernel weight and yield and yield components of wheat plants as compared to conventional tillage. Wheat plants resulted in a significant increase in tillers m-2 and accumulated higher biomass and grain yield under 15-cm row spacing than all three other row spacing. The grain yield increase was mainly attributed to more tillers m-2 at 15-cm than the other row spacing. So, zero tillage and narrow row spacing (15 cm) proved to be involved in higher wheat yield for the wheat-maize cropping system in semi-arid regions.